Van Halen, brown M&M's, and quality control - Venkataraman, Ray R. (SAGE Knowledge. Cases., 2017)
This case describes how the rock band, Van Halen, used the presence of brown M&Ms in the backstage area as a visible signal to quality lapses of conformance to its performance specifications.